SURVEY OF KNOWLEDGE AND ATTITUDES ON PREVENTION OF CERVICALCANCER - Terzieva, Galina (Journal of process management and new technologies, 2016)
Cancer of the cervix is the second most common cause of death among women of malignancies after breast cancer. Human Papilloma Virus (HPV) is transmitted through sexual contact (vaginal, anal and oral) and in contact skin-skin in the genital area. It is highly resistant to environmental conditions and is therefore widespread. Every sexually active woman is at risk. HPV is transmitted from man to woman and in most cases the infection is asymptomatic from 6 to 15 years after the time of infection, which further contributes to the spread of the virus. The aim of the research is exploring the opinion of students and their parents about the use of a vaccine to prevent cervical cancer. The subject of the research is the process of building a culture of health of young people and their subject position for participation in health prevention. Objects of the survey are the attitudes, knowledges and assessment of different social groups for protection and preservation of their health and the health of others. Scope of the research are 141 respondents: students and their parents. Approaches and methods for the study of the problem: theoretical analysis of the problem in the medical literature; documentary research; anonymous questionnaire survey; comparative analysis. Results of the study outline the unwillingness of the majority of parents - 54% to vaccinate their daughters. 62.3% of students said they "would not be vaccinated because the vaccine is considered as dangerous to health, and because there are not enough studies about the benefits of it."